2020
DOI: 10.1042/bst20191255
|View full text |Cite|
|
Sign up to set email alerts
|

New perspectives of the cardiac cellular landscape: mapping cellular mediators of cardiac fibrosis using single-cell transcriptomics

Abstract: Single-cell transcriptomics enables inference of context-dependent phenotypes of individual cells and determination of cellular diversity of complex tissues. Cardiac fibrosis is a leading factor in the development of heart failure and a major cause of morbidity and mortality worldwide with no effective treatment. Single-cell RNA-sequencing (scRNA-seq) offers a promising new platform to identify new cellular and molecular protagonists that may drive cardiac fibrosis and development of heart failure. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…However, in these contexts, fibroblast gene expression and phenotype are distinct [ 22 ]. For example, in myocardial infarction (MI), fibroblasts rapidly differentiate into activated fibroblasts and myofibroblasts—both well-established drivers of cardiac ECM deposition [ 23 ]. Conversely, we have recently reported that myofibroblasts are absent during the development of chronic fibrosis in angiotensin II-induced cardiac remodelling [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in these contexts, fibroblast gene expression and phenotype are distinct [ 22 ]. For example, in myocardial infarction (MI), fibroblasts rapidly differentiate into activated fibroblasts and myofibroblasts—both well-established drivers of cardiac ECM deposition [ 23 ]. Conversely, we have recently reported that myofibroblasts are absent during the development of chronic fibrosis in angiotensin II-induced cardiac remodelling [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…(K) A schematic model. (Krstevski et al, 2020). We show here that Twist1 is responsible for Clca2 trans-repression in activated cardiac fibroblasts by directly binding to the E-box element located on the Clca2 promoter (Figure 5K).…”
Section: Discussionmentioning
confidence: 59%
“…Recent investigations have provided irrefutable evidence to support resident fibroblasts as the primary source of myofibroblasts contributing to cardiac fibrosis ( Travers et al, 2016 ). Dynamic transcriptomic changes highlight the transition from quiescent cardiac fibroblasts to mature myofibroblasts ( Krstevski et al, 2020 ). We show here that Twist1 is responsible for Clca2 trans- repression in activated cardiac fibroblasts by directly binding to the E-box element located on the Clca2 promoter ( Figure 5K ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have implicated cardiac broblasts in diabetic cardiomyopathy, however their precise role in diabetes in vivo is still unknown. Cardiac broblasts are the primary cell type involved in deposition of extracellular matrix (ECM) in both states of acute injury or chronic stress [21]. However, in these contexts, broblast gene expression and phenotype are distinct [13].…”
Section: Discussionmentioning
confidence: 99%